Homonymy and triple homonymy among species names of fossil Flabellum corals (Scleractinia: Flabellidae), with proposals for their replacement names - Collado, Gonzalo A.; Galleguillos, Fernando F.; Hoeksema, Bert W. (Journal of paleontology, 2025)
According to the International Code of Zoological Nomenclature (ICZN, 1999), the Principle of Homonymy (Article 52) states that when two or more taxa are distinguished from each other, they must not be denoted by the same name because this would cause confusion. Consequently, in a case of homonymy, only the senior name may be used as valid (Art. 52.2). The ICZN (1999) also indicates that if the rejected junior homonym has no known available and potentially valid synonym, it must be replaced by a new substitute name (Art. 60.3), that is, a replacement name.